Identification of potential SARS-CoV-2 entry inhibitors by targeting the interface region between the spike RBD and human ACE2 - Arun Bahadur Gurung; Mohammad Ajmal Ali; Joongku Lee; Mohammad Abul Farah; Khalid Mashay Al-Anazi (Elsevier, 2021)
Coronavirus disease 2019 (COVID-19) is a fatal infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The virus infection is initiated upon recognition and binding of the spike (S) protein receptor-binding domain (RBD) to the host cell surface receptor, angiotensin-converting enzyme 2 (ACE2). Blocking the interaction between S protein and ACE2 receptor is a novel approach to prevent the viral entry into the host cell. The present study is aimed at the identification of small molecules which can disrupt the interaction between SARS-CoV-2 S protein and human ACE2 receptor by binding to the interface region. A chemical library consisting of 1,36,191 molecules were screened for drug-like compounds based on Lipinski's rule of five, Verber's rule and in silico toxicity parameters. The filtered drug-like molecules were next subjected to molecular docking in the interface region of RBD. The best three hits viz; ZINC64023823, ZINC33039472 and ZINC00991597 were further taken for molecular dynamics (MD) simulation studies and binding free energy evaluations using Molecular mechanics-Poisson-Boltzmann surface area (MM-PBSA) and Molecular mechanics-Generalized Born surface area (MM-GBSA). The protein-ligand complexes showed stable trajectories throughout the simulation time. ZINC33039472 exhibited binding free energy value lower as compared to the control (emodin) with a higher contribution by gas-phase energy and van der Waals energy to the total binding free energy. Thus, ZINC33039472 is identified to be a promising interfacial binding molecule which can inhibit the interaction between the viral S protein and human ACE2 receptor which would consequently help in the management of the disease.